Age-friendly cities and communities : a global perspective - Buffel, Tine, ....-; Handler, Sophie, ....-; Phillipson, Chris, 1949- (Bristol : Policy Press, 2018)
This important book provides a comprehensive survey of different strategies for developing age-friendly communities, and the extent to which older people themselves can be involved in the co-production of age-friendly policies and practices.
Keywords: Ouderen ; wonen